2022
DOI: 10.1111/ans.17975
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐arm assisted total knee arthroplasty has a learning curve of 16 cases and increased operative time of 12 min

Abstract: Background: Robotic-arm assisted systems are increasingly used for knee arthroplasty, however introduction of new systems can involve a learning curve. We aimed to define the learning curve in terms of operative time and component placement/sizing of a robotic system for total knee arthroplasty (TKA) in a team of experienced surgeons, and to investigate mid-term patient outcomes. Methods: A total of 101 consecutive patients underwent primary robotic-arm assisted TKA by three surgeons (mean 2 year follow-up). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(73 reference statements)
3
6
0
Order By: Relevance
“…Similarly, the learning curve of robotically-assisted TKA (RA-TKA) systems determined by LC-CUSUM analysis of operative times has been reported between 7 and 43 cases. [23][24][25][26] The range of reported learning curves for these RA-TKA systems is similar to both that CT-based RA-THA and of this present study, illustrating the comparable adoption characteristics of robotic technologies into orthopaedic surgery workflows across techniques.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, the learning curve of robotically-assisted TKA (RA-TKA) systems determined by LC-CUSUM analysis of operative times has been reported between 7 and 43 cases. [23][24][25][26] The range of reported learning curves for these RA-TKA systems is similar to both that CT-based RA-THA and of this present study, illustrating the comparable adoption characteristics of robotic technologies into orthopaedic surgery workflows across techniques.…”
Section: Discussionsupporting
confidence: 80%
“…The similarity of our results to that in the current literature suggests that the adoption of fluoroscopy‐based RA‐THA is no more complex or difficult than that of CT‐based robotic systems. Similarly, the learning curve of robotically‐assisted TKA (RA‐TKA) systems determined by LC‐CUSUM analysis of operative times has been reported between 7 and 43 cases 23–26 . The range of reported learning curves for these RA‐TKA systems is similar to both that CT‐based RA‐THA and of this present study, illustrating the comparable adoption characteristics of robotic technologies into orthopaedic surgery workflows across techniques.…”
Section: Discussionsupporting
confidence: 72%
“…The infection risk has been also documented with respect to the operative time [49], another debated aspect in the comparison of R‐TKA and C‐TKA. Most studies suggest longer operative time in R‐TKA, mainly due to registration and bone preparation stages of the R‐TKA surgical procedure [55, 60]. The present meta‐analysis confirmed a statistically significant difference in terms of operative time in favour of C‐TKA.…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, a recent analysis of high-volume arthroplasty surgeons has found that the transition to robotic instrumentation substantially increased surgery times, even over the long term [ 8 ]. Studies on the transition to other robotic TKA solutions found learning curves of anywhere between six and 16 surgeries [ 6 , 7 ]. In our study, robotic surgery times were equal to traditional instrumentation after just two robotic surgeries (Figure 1 and Table 5 ); unlike the studies previously mentioned, we did not see a gradual reduction in robotic surgery times with an eventual plateau.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of surgeons transitioning to robotic approaches showed that surgeons took 6-11 surgeries to learn the new techniques and stabilize surgery times [ 6 ]. Additionally, a study evaluating the learning curve of a popular image-based robotic solution found a learning curve of 16 surgeries across three different mediums for high-volume surgeons [ 7 ]. Previous research has shown that among high-volume arthroplasty surgeons, robotics significantly increase a surgeon’s time in the operating room [ 8 ].…”
Section: Introductionmentioning
confidence: 99%